Pola Komunikasi Rasulullah SAW dalam Menetapkan Hukuman Pelaku Persetubuhan di Siang Hari Ramadhan - Aflah Agan Hasibuan (Al-Balagh : Jurnal Komunikasi Islam, 2024)
This research aims to find out the punishment for people who have sexual intercourse during the day in the month of Ramadan and the communication patterns of the Prophet Muhammad in resolving cases of sexual intercourse during the day during the month of Ramadhan. The research method used in this research is library research with a historical, normative theological and sociological approach. The results of the research show that the punishment for people who have sexual intercourse during the day in the month of Ramadan is: freeing their servants, fasting for two consecutive months and feeding sixty poor people. The punishment is in accordance with the limits of the abilities of the person being punished. The communication pattern of Rasulullah SAW in resolving cases of sexual intercourse during the day during the month of Ramadan was a verbal communication pattern in the nature of Q & A (question and answer) and gift away.